Interleukin-36 potently stimulates human M2 macrophages, Langerhans cells and keratinocytes to produce pro-inflammatory cytokines. (August 2016) - Dietrich, Damien; Martin, Praxedis; Flacher, Vincent; Sun, Yu; Jarrossay, David; Brembilla, Nicolo; Mueller, Christopher; Arnett, Heather A.; Palmer, Gaby; Towne, Jennifer; Gabay, Cem
Highlights: IL-36 is as potent as IL-1 in stimulating M2 macrophages and Langerhans cells. Macrophages respond differently to IL-36 and IL-1 according to their polarization. The response of M2 macrophages to IL-1 is impaired by an autocrine effect of IL-1Ra. Abstract: Interleukin (IL)-36 cytokines belong to the IL-1 family and include three agonists, IL-36 α, β and γ and one inhibitor, IL-36 receptor antagonist (IL-36Ra). IL-36 and IL-1 (α and β) activate similar intracellular pathways via their related heterodimeric receptors, IL-36R/IL-1RAcP and IL-1R1/IL-1RAcP, respectively. However, excessive IL-36 versus IL-1 signaling induces different phenotypes in humans, which may be related to differential expression of their respective receptors. We examined the expression of IL-36R, IL-1R1 and IL-1RAcP mRNA in human peripheral blood, tonsil and skin immune cells by RT-qPCR. Monocyte-derived dendritic cells (MDDC), M0, M1 or M2-polarized macrophages, primary keratinocytes, dermal macrophages and Langerhans cells (LC) were stimulated with IL-1β or IL-36β. Cytokine production was assessed by RT-qPCR and immunoassays. The highest levels of IL-36R mRNA were found in skin-derived keratinocytes, LC, dermal macrophages and dermal CD1a + DC. In the blood and in tonsils, IL-36R mRNA was predominantly found in myeloid cells. By contrast, IL-1R1 mRNA was detected in almost all cell types with higher levels in tonsil and skin compared to peripheral blood immune cells. IL-36β was as potent as IL-1β in stimulating M2 macrophages, keratinocytes and LC, less potent than IL-1β in stimulating M0 macrophages and MDDC, and exerted no effects in M1 and dermal macrophages. Levels of IL-1Ra diminished the ability of M2 macrophages to respond to IL-1. Taken together, these data are consistent with the association of excessive IL-36 signaling with an inflammatory skin phenotype and identify human LC and M2 macrophages as new IL-36 target cells.